Nucleobase pairing and photodimerization in a biologically derived metal-organic framework nanoreactor - Samantha L. Anderson (Nature Portfolio, 2019)
Metal-organic frameworks have shown promise as nanoreactors, facilitating the synthesis of molecules that are otherwise difficult to isolate. Here, the authors design a framework featuring unobstructed adenine linkers to which thymine molecules can base-pair, allowing for thymine dimerization in the pores upon UV irradiation.